DegoViz: An Interactive Visualization Tool for a Differentially Expressed Genes Heatmap and Gene Ontology Graph - Somyung Oh (Applied Sciences, 2017)
Microarray is a general scheme to identify differentially expressed genes for a target concept and can be used for biology. The output is presented utilizing a heatmap that biologists analyze in related terms of gene ontology to determine the characteristics of differentially expressed genes. In this paper, we propose an integrated visualization tool for a heatmap and gene ontology graph. Most of the previous methods used were static and none of them were combined. The proposed visualization tool integrates these and provides users with an interactive management ability. Users can easily identify and confirm related terms of gene ontology for given differentially expressed genes. Further, the proposed tool visualizes the connections between genes on the heatmap and gene ontology graph. Therefore, the proposed tool can be used for precision healthcare.